The Dharma in DNA: intersections between biology and Buddhism - Denver, Dee (Oxford University Press, 2022)
1. Water -- 2. Trees -- 3. Truths -- 4. Intersections I -- 5. Intersections II -- 6. Sciences -- 7. Molecules -- 8. Identities -- 9. Bodhi -- 10. Intimacy -- Glossary.